2019
DOI: 10.1002/ange.201912219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on the Nucleation and Growth of Precious Metal Nanocrystals

Abstract: Understanding the effect of physical parameters (e.g., temperature) on crystallisation dynamics is of paramount importance for the synthesis of nanocrystals of well‐defined sizes and geometries. However, imaging nucleation and growth is an experimental challenge owing to the resolution required and the kinetics involved. Here, by using an aberration‐corrected transmission electron microscope, we report the fabrication of precious metal nanocrystals from nuclei and the identification of the dynamics of their nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…[ 63 ] Different studies have suggested a tenfold variation in the nucleation rates due to assumption of constant Jo${J}_o$ values at normal temperature points. [ 12–64 ] Consequently, computation of Jo${J}_o$ was performed by determining Aα0.33emand0.33emEα${A}_{\alpha}\ \mathrm{and}\ {E}_{\alpha}$, using experimentally generated TGA data. A precise value of apparent activation energy false(Eαfalse)$( {{E}_\alpha } )$ of nucleation for CCPN matrix is computed by iterative procedure (Equation (16)) and provided in Table 2 and Table S2 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 63 ] Different studies have suggested a tenfold variation in the nucleation rates due to assumption of constant Jo${J}_o$ values at normal temperature points. [ 12–64 ] Consequently, computation of Jo${J}_o$ was performed by determining Aα0.33emand0.33emEα${A}_{\alpha}\ \mathrm{and}\ {E}_{\alpha}$, using experimentally generated TGA data. A precise value of apparent activation energy false(Eαfalse)$( {{E}_\alpha } )$ of nucleation for CCPN matrix is computed by iterative procedure (Equation (16)) and provided in Table 2 and Table S2 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[ 18 ] The nucleation rate of ultra‐small osmium clusters to ultra‐small crystals was computed by increment of temperature from 20 °C (1.02 nm) to 100 °C (1.31 nm), to be 78.8–176.5 pm min −1 , respectively. [ 19 ] In spite of above findings, there is no engineered technology to compute nucleation rate of ultra‐small clusters at higher temperature (>100 °C). Thus, to make it possible, here we use the TGA technology for computation of nucleation rate false(nuclei0.33emμm20.33emmin1false)$(\mathrm{nuclei}\ \umu{\mathrm{m}}^{-2}\ {\mathrm{\min}}^{-1})$ at higher temperature, as a first‐time approach.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations